2014
DOI: 10.1183/09031936.00002414
|View full text |Cite
|
Sign up to set email alerts
|

Impaired arm activity in COPD: a questionable goal for rehabilitation

Abstract: The most common extrapulmonary problems in chronic obstructive pulmonary disease (COPD) patients are cardiovascular comorbidities, muscle weakness and dysfunction [1][2][3]. Indeed, the reduced peripheral muscle mass and strength increase patient's symptoms during effort (fatigue and or dyspnoea) and progressively lead to disability. Furthermore, both lower and upper limb dysfunction has been shown to independently predict the long-term prognosis of COPD patients [2].The use of arms is involved in many daily d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Although early guidelines suggest that unsupported arm training should be included as a component of pulmonary rehabilitation (PR) for patients with COPD , most recent PR guidelines for standard programmes do not specifically suggest the inclusion of arm training . Two major identified problems are inappropriateness of methods to assess impairment in defining the contribution of arm training in COPD and the probable mechanisms by which training improves arm function . Arm strength training leads to moderate improvements in peripheral muscle strength in COPD patients, but there is a lack of high‐quality studies supporting the claim that arm strength training improves functional arm tasks .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although early guidelines suggest that unsupported arm training should be included as a component of pulmonary rehabilitation (PR) for patients with COPD , most recent PR guidelines for standard programmes do not specifically suggest the inclusion of arm training . Two major identified problems are inappropriateness of methods to assess impairment in defining the contribution of arm training in COPD and the probable mechanisms by which training improves arm function . Arm strength training leads to moderate improvements in peripheral muscle strength in COPD patients, but there is a lack of high‐quality studies supporting the claim that arm strength training improves functional arm tasks .…”
Section: Introductionmentioning
confidence: 99%
“…The effects of arm training on patients’ functional performance in daily life have not been extensively studied . Further well‐designed studies that have sufficiently strong and clinically meaningful outcome measurements are necessary . Therefore, this study aimed to investigate the effect of arm strength training, implemented without general exercise training, on arm exercise capacity, ADL and occupational performance in patients with COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral muscle dysfunction is one of the most common extrathoracic manifestations of COPD and has been associated with poor prognosis. (1) Studies have shown that a reduction in muscle mass and strength is a predictor of mortality (2,3) and a marker of exacerbation risk in COPD patients. (4) The cause of peripheral muscle dysfunction is multifactorial, the main factors involved being physical inactivity, malnutrition, exacerbations, and corticosteroid use.…”
Section: Introductionmentioning
confidence: 99%